Canon and Toshiba go their own way in flat panels. - Boyd, J. (IEEE spectrum)
The article presents the alliance between the Canon Inc. and Toshiba Corp., both in Tokyo. The alliance was formed to meet the soaring demand of the consumers on large flat-panel screens. They intend to produce and market large flat-panel screens for TVs based on surface-conduction electron-emitter display (SED) technology. This technology is newcomer to the big-screen wars, which have been dominated by liquid-crystal displays (LCD), follower by plasma displays, and projection TVs using cathode ray tube (CRT). This article also presents the advantages of SED technology over LCDs, CRTs and plasma displays.